Kesediaan Menerima Pembayaran Jasa Lingkungan Air Sub Das Way Betung Hulu Oleh Masyarakat Kawasan Hutan Register 19 (Studi Kasus Di Desa Talang Mulya Kecamatan Padang Cermin Kabupaten Pesawaran) - Faisal Arafat; Christine Wulandari; Rommy Qurniati (Department of Forestry, Faculty of Agriculture, University of Lampung, 2015)
One of the solution utilize to overcome damage of DAS Way Betung hydrology function is apply of Payment for Environmental Service (PES) for forest and land rehabilitation. PES is needs to be studied more in depth, especially the level of value willingness to accept payment by people as environmental service provider. The purposes of this research are knowing value of willingness to accept (WTA) the people regarding PES of upstream Sub DAS Way Betung and factors to influence it with knowing incentive forms who wanted by the people. Method used in this research are Willingness to Accept analysis, regression analysis and descriptive analysis qualitative. Based on the result, the average of WTA respondent in the location of research is Rp 8,552.63 per tree per year. If the number of trees in the mix community garden is 1,462 trees, then it will be obtained the total value of WTA Talang Mulya village is Rp 12,503,945.06 per year. Factors which significant influenced to WTA value that are level education, age and status of arable land. Incentive forms who wanted by respondent are cash money, rural development, seedlings and fertilizer donations and also farm animal. Keywords: payment for environmental service, WTA, DAS Way Betung